PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH (SKPD) PADA PEMERINTAH KABUPATEN TULUNGAGUNG - Adib Laga Widigdo (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Budgeting participation has been attracting researcher’s attention for several years. Some prior studies still show inconsistency and contra results between budgeting participation and managerial performance. This study will re-exam the effect of budgeting participation to managerial performance. Survey was conducted to collect data that was distributed to 58 plan and budget managers on Satuan Kerja Perangkat Daerah (SKPD) as the division of Tulungagung Government. Purposive sampling method was chosen due to manager’s main duty in planning and budgeting process. Only 50 questioners were analyzed of 58 ones. While, simple regression was chosen as the analysis model. The result indicated that budgeting participation had effect toward managerial performance. It also showed that budgeting participation had positive effect toward managerial performance. Therefore, the government had to intensify the budgeting participation in order to increase the managerial performance.